Depressive symptoms in parents are associated with reduced empathy toward their young children - Salo, Virginia C. (PLoS One, 2020)
BACKGROUND: While depression is typically associated with reduced levels of empathy, this association differs depending on how empathy is measured. Given the importance of empathy in the parent–child relationship, we sought to examine whether the associations between depression and dispositional empathy would also extend to empathy towards one’s own child. METHODS: Within a non-clinical sample of 150 parents of young children, we examined the associations between self-reported depressive symptoms, dispositional empathic tendencies, and empathy specifically toward their own children, and how these associations might differ based on parent gender. RESULTS: Depressive symptoms were related to lower levels of cognitive and affective empathy, and higher levels of empathic distress. Over and above the association with dispositional empathy, depressive symptoms were associated with reduced levels of parents’ affective empathy toward their own child. The associations between depressive symptoms and both dispositional and own-child specific empathy varied by parent gender. For fathers, depressive symptoms predicted own-child specific affective empathy, over and above dispositional affective empathy, while for mothers, depressive symptoms predicted own-child specific empathic distress, over and above dispositional empathic distress. CONCLUSIONS: The current findings provide further indication that caregivers with elevated depression may engage in patterns of thoughts and behaviors that have implications for their interactions with their children. Parents’ experienced empathy toward their own child may be one mechanism by which depression impacts the early caregiving environment, and thus may be an important target for intervention in improving the early caregiving experiences for children at elevated risk due to parental depression. Differences in cognitive and affective empathy found among those with depression may be even more pronounced in the thoughts and feelings towards one’s own child, making this an important clinical target.